Production and decomposition rates of different fen species as targets for restoration. (August 2018) - Bérubé, Vicky; Rochefort, Line
Highlights: We studied rich fen NPP and decomposition as indicators for restoration monitoring. Contribution to NPP in decreasing importance: roots, bryophytes, trees, herbs and shrubs. Bryophyte reintroduction could help to reach the restoration goal of carbon sequestration. Species with high root production, such as graminoids, should be selected for restoration. Hummock plant community had a higher peat accumulation potential. Abstract: There is an increasing interest in considering ecosystem processes after fen restoration, and not solely species composition. To evaluate the success of ecological restoration, comparisons with targets from reference ecosystems are required. We documented net primary production (NPP) and decomposition of the main vegetation components in order to describe a reference data set for ecological restoration of moderately rich to rich minerotrophic peatlands (fens) in southeastern Canada. Data collection included three growing seasons for herbs and shrubs and two growing seasons for belowground biomass, trees and bryophytes. Average NPP for above and belowground biomass of three selected natural basin fens were 450 g m −2  yr −1 . Belowground NPP represented 45% of the total NPP. Sphagnum warnstorfii was the most productive bryophyte (140 g m −2  yr −1 ) and the slowest plant species to decompose (exponential decomposition constant k  = 0.07 yr −1 ). The brown mosses Tomenthypnum nitens, Campylium stellatum and Scorpidium cossonii had a NPP of 79, 69 and 92 g m −2  yr −1, respectively, and decomposed at the same rate (identical k values of 0.14 yr −1 ). Trees covered a large surface area in the fens, with an average NPP of 73 g m −2  yr −1 . S. warnstorfii contributed to hummocks having a higher peat accumulation potential than lawn vegetation. The graminoid Trichophorum cespitosum significantly increased NPP in lawns and should be targeted in restoration plans for fens. To restore peat accumulating processes (production and decomposition) in fens, bryophytes should be the primary focus for re-introduction, specifically species that are adapted to living in drier conditions, such as hummock species. The range of variability for NPP and decomposition established by this study should be considered as a decision tool in restoration projects to monitor restored ecosystems trajectories and successes.